Pan Africa Bean Research Alliance 2015-2020 Results - Pan-Africa Bean Research Alliance (2022)
Pan Africa Bean Research Alliance (PABRA) has been over 25 years working with partners in 31 countries to breed better beans for Africa through agricultural research for development.